(untitled) (Research, Society and Development, 2021)
Introduction: The Inflammatory Bowel Disease (IBD) corresponds to a series of conditions that involve inflammation of the gastrointestinal tract, mainly in the intestine, becoming red, swollen and with the presence of ulcers. It is divided into two groups: Ulcerative Colitis and Crohn’s Disease. Objective: To identify the importance of an adequate food strategy in promoting the quality of life of patients with Inflammatory Bowel Diseases, what are these diseases and their symptoms, what is the best nutritional strategy for patients with Inflammatory Bowel Diseases during treatment and to correlate the improvement in quality of life with the use of the nutritional strategy in patients with IBD. Methodology: The qualitative research method was used. Results and discussion: The IBD have treatments in the resources of medication, food, nutritional supplementation, conventional therapy and, in the last case, surgery to try to solve the improvement of symptoms in patients who do not respond to alternative treatments offered. Conclusion: The direct correlation of nutrition with the improvement in the quality of life of patients affected by inflammatory bowel diseases is still scarce, however, through the analysis of treatment with the multidisciplinary team, it is possible to observe a contribution to the stability of patients. Interdisciplinary care, the humanized and integral look of health professionals towards patients is necessary, as well as the development of new studies focused on the theme.